2012
DOI: 10.1007/s12178-012-9145-8
|View full text |Cite
|
Sign up to set email alerts
|

Sports injuries of the wrist

Abstract: Sports injuries involving the hand and wrist are common and, as a result, many different practitioners (athletic trainers, physical therapists, primary care physicians, general orthopedic surgeons) will encounter these injuries. In addition to thorough evaluation, an understanding of typical pathologies seen in the athlete enhances diagnosis and facilitates appropriate, expedient management. These injuries are complex because they can be either acute traumatic or repetitive in origin and often involve both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…39 Although research has long been directed at elucidating noncontact ACL injury mechanisms, the role of repetitive loading has received little attention. 33 Many joints in the human body are susceptible to repetitive loading injuries, including the wrist, 11 shoulder, 3 elbow, 10 intervertebral disc, 38 and hip. 5 In fact, failures due to tissue fatigue have been reported in the leporine medial collateral ligament 41 and the human extensor digitorum longus tendon.…”
mentioning
confidence: 99%
“…39 Although research has long been directed at elucidating noncontact ACL injury mechanisms, the role of repetitive loading has received little attention. 33 Many joints in the human body are susceptible to repetitive loading injuries, including the wrist, 11 shoulder, 3 elbow, 10 intervertebral disc, 38 and hip. 5 In fact, failures due to tissue fatigue have been reported in the leporine medial collateral ligament 41 and the human extensor digitorum longus tendon.…”
mentioning
confidence: 99%
“…[282930] In our study, we carried out the direct MRAr in one specimen, and in the sagittal plane, we could find the UT, UL ligaments, and the volar and dorsal capsules more clearly than conventional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested it as critically important for practitioners to show greater awareness towards use of physical examination and false positives for corroborating the diagnostic imaging [10,11]. Previous studies demonstrate a difference in the accuracy of MRI in diagnosing these injuries [9]. Multiple factors can play a major role in MRI accuracy in detecting TFCC lesions; the magnetic field strength is one of these factors as it was shown by Anderson et al who suggested that imaging with 3.0 T offers higher quality at a given spatial resolution [10].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is applied when there is persistence of pain which prevents athletes from their performance. Due to the fact that MRI show higher sensitivity towards detection of TFCC abnormalities and lesions, the MRI arthrogram has been found to be specifically significant for precisely detecting the clinically relevant TFCC tears through the overflow of contrasting leakage directed from the ulnocarpal joint into the DRUJ [9]. Using radiography for evaluating purely soft tissue TFCC injury may not possible lead to demonstrate pathognomonic abnormalities, but rather may result in demonstrating secondary findings such as fracture in the ulnar styloid or positive ulnar variance.…”
Section: Introductionmentioning
confidence: 99%